David N. Lorenzen, El flagelo de la Misión: Marco della Tomba en Indostán, México, El Colegio de México, 2010, 223 pp. - Staples, Anne (Estudios de Asia y África, 2011)
David N. Lorenzen, El flagelo de la Misión: Marco della Tomba en Indostán, México, El Colegio de México, 2010, 223 pp.